Peran Ekonomi Syariah Terhadap UMKM di Indonesia - Izzatil Najwa; Dafiar Syarif (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
This research aims to comprehensively examine the role of Islamic economics in empowering Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using the Systematic Literature Review (SLR) method, this study analyzes scholarly articles published between 2020-2024 that address the relationship between Islamic economic principles and MSME development. The findings reveal that Islamic financial institutions, particularly Islamic banking and Sharia Savings and Financing Cooperatives (KSPPS), play a strategic role in providing capital access through various Islamic financing schemes such as musyarakah and mudharabah. The implementation of Islamic economic principles in MSMEs has demonstrably enhanced business performance, sales growth, and consumer loyalty toward halal products. This research contributes valuable insights for policymakers and practitioners in developing Islamic finance as a catalyst for creating independent, inclusive, and sustainable MSMEs in the digital era. Islamic economics proves to be not merely an alternative system but an essential framework for ethical and sustainable business practices in Indonesia's MSME sector.